The lively accretion disc in NGC 2992 – II. The 2019/2021 X-ray monitoring campaigns. Issue 2 (18th May 2022) - Middei, R; Marinucci, A; Braito, V; Bianchi, S; De Marco, B; Luminari, A; Matt, G; Nardini, E; Perri, M; Reeves, J N; Vagnetti, F
ABSTRACT: We report on the short- and long-term X-ray properties of the bright nearby Seyfert 2 galaxy NGC 2992, which was extensively observed with Swift,   XMM–Newton, and NuSTAR .  Swift targeted the source more than 100 times between 2019 and 2021 in the context of two monitoring campaigns. Both time-averaged and time-resolved analyses are performed, and we find that the short-to-long term spectral properties of NGC 2992 are dominated by a highly variable nuclear continuum. The source varied in the 2–10 keV energy band from 0.6 to 12 × 10 −11 erg cm −2 s −1 during the two year long Swift monitoring. The fastest 2–10 keV flux change (by a factor of $\sim 60{{\ \rm per\ cent}}$ ) occurred on a time-scale of a few hours. The overall emission spectrum of the source is consistent with a power law-like continuum (Γ = 1.69 ± 0.01) absorbed by a constant line-of-sight column density N H  = (7.8 ± 0.1) × 10 21 $\rm cm^{-2}$ . The reflected emission is likely due to matter with an average column density N H  = (9.6 ± 2.7) × 10 22 $\rm cm^{-2}$, thus NGC 2992 appears to have a globally Compton-thin circumnuclear medium. This scenario is fully supported by an independent analysis of the fractional variability and by XMM–Newton multiyear spectra.